Ending Analysis : Theory and Technique. - De Simone, Gilda (Karnac Books, 1997)
This book, beyond dealing with the theoretical and technical questions concerning the termination of analysis, gives a picture of the particular nature of the psychoanalytic cure in relation to the therapies that have come forth from psychoanalytic roots. The theoretical work is supported by rich clinical details.